2001
DOI: 10.2190/7n22-5muc-4mvc-ncqq
|View full text |Cite
|
Sign up to set email alerts
|

Marital Relationships in Late Adulthood: Synchronous versus Asynchronous Couples

Abstract: The article presents a study on marital relations in late adulthood, conducted among a sample of 469 Israeli couples, who were divided into four groups based on occupational status and spousal timing of retirement. Two of the groups were categorized as synchronous: pre-retired couples (both partners are close to retirement); and retired couples (both partners are retired), and two of the groups were categorized as asynchronous: employed husband/retired wife and retired husband wife/employed husband. Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…This suggests that retirement is perceived by both husband and wife as not being a negative transition for couples. This is consistent with previous research on retirement and marital satisfaction (Ekerdt & Vinick, 1991;Kulik, 2001;Miller, Peterson, & Bengtson, 1998;Moen, Kim, & Hofmeister, 2001), which generally found few negative effects of retirement on marital quality.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that retirement is perceived by both husband and wife as not being a negative transition for couples. This is consistent with previous research on retirement and marital satisfaction (Ekerdt & Vinick, 1991;Kulik, 2001;Miller, Peterson, & Bengtson, 1998;Moen, Kim, & Hofmeister, 2001), which generally found few negative effects of retirement on marital quality.…”
Section: Discussionsupporting
confidence: 92%
“…After retirement, they wanted to increase their life satisfaction through being with their family members and meeting their needs. Many previous studies have shown that retirement leads to increased interactions with family and friends (55,(57)(58)(59). Andrews et al defined three factors that influence this adaptation as; profession-related stress, inflexible work hours and salary (15).…”
Section: Discussionmentioning
confidence: 99%
“…While retired nurses received emotional support from their families (25). Some studies indicated that retired nurses were faced with a reduced standard of living (63,67): however, the results of Kulik's study showed that the living conditions of retired people were not changed (57). This study explored the retirement adjustment process according to the knowledge and experiences of retired Iranian nurses.…”
Section: Discussionmentioning
confidence: 99%
“…In more traditional, non-Western countries, husbands were likely to make the family decisions. Similarly, in her study of marital relationships in Israel, Kulik (2001) found that retired as well as nonretired Israeli couples, were overall egalitarian in their decision making. She also observed that just as has been reported in United States both societies encourage dual earner families and view job opportunities and professional activities for women in a positive light.…”
Section: Application Of the Model To Marital Relationshipsmentioning
confidence: 93%